Bimetal Fuels for Energetic Materials Chap. 7 - Korotkikh A. G. Aleksandr Gennadievich; Glotov O. G. Oleg; Sorokin I. V. Ivan Viktorovich; Arkhipov V. A. Vladimir Afanasjevich (2020, 2020)
Title screen